El Nobiliario vero y el pensamiento aristocrático del siglo XV - Mexía, Fernando, active 15th century (Medievalia Hispanica, 2019)
The first critical edition of Mexía's Nobiliario, with an introduction, notes and bibliography by José Julio Martín Romero.